HYDROLOGICAL FEATURES OF THE ARABIAN SEA OFF THE NORTHERN AND CENTRAL WEST COAST OF INDIA DURING 1964 WINTER - Rao, D S; Kunhikrishnan, N P; Kumar, R Vasantha (Indian Journal of Fisheries, 2011)
The hydrographic features prevailing along the northern and central west coast of India during the early part of winter 1964 are discussed. A weak northward gradient in temperature north of 17Â°N and an eastward gradient south of it is noticed. The thermocline is found at shallower depths in the northern regions. A steady increase in the salinity is observed northward, the maximum being off Bombay. North of 17Â°N the flow is mainly eastwards which deflects towards south with increase in depth. At SO m a continuous weak southward drift is noticed. More or less uniform distribution is foimd in the dissolved oxygen content at surface and 20 m depth, but at 50 m depth eastward gradients are noticed. Sharp decrease in dissolved oxygen values occur from the top of the thermocline and the oxygen minimum layer is conspicuous in all the sections. The nature of the isotherms and the isolines of oxygen indicate the presence of upwelling in the region off Bombay.